The use of high resolution images in mapping of landscapes affected by erosion - Stefanuto, Estêvão Botura [UNESP]; Lupinacci, Cenira Maria [UNESP] (Universidad de Jaen, 2023)
The linear erosive features, can be understood as a result of this relation between natural and man-made elements. Thus, the aim is to analyze a landscape with erosion features from high resolution images recorded by a DJI MAVIC Pro UAV with a RGB CMOS sensor of 12.35M effective pixels. The results, show possibility of identifying degree of dynamism of erosive gullies sidewall as well as for an increase in detailing erosive systems linked to ravines. The similarity between the phenomena identified in field and those present in the image is also interesting and constitutes a factor that drastically reduces the onus over the reambulation steps. A few limitations were identified, such as the need for some field verifications to characterize topographic ruptures with water flow and limitations in the photointerpretation process, caused, for example, by obstruction in the field of view.
El uso de imágenes de alta resolución en la elaboración de mapas de paisajes afectados por la erosión
L'utilisation d'images haute résolution dans la cartographie des paysages affectés par l'érosion
Keywords: Geomorphological Features; Linear Erosive Features; UAV